Penggunaan Beberapa Komposisi Spektrum Led Pada Potensi Dan Hasil Hidroponik Indoor Selada Keriting Hijau - Daru Nurdianna; Retno Bandriyati Arni Putri; Dwi Harjoko (Universitas Sebelas Maret, 2018)
This study aims to determine the differences in the growth response of green curly lettuce to the differentiation treatment of LED lighting with different spectrum in indoor hydroponics. The research was conducted from October to November 2017. The experimental design used was experimental with 1 lighting factor with 5 levels, there are sunlight (P0), LED 20% blue: 80% red (P1), LED 80% blue: 20% red (P2), 50% blue LED: 50 % red (P3), and 100% white daylight (P4). Observational variables included plant height, leaf number, leaf area, leaf color, total wet weight, leaf wet weight, wet root weight and dry weight of the plant. The result of this experiment showed that LED irradiation have affect the treatment are plant height, leaf number, leaf area, chlorophyll content, fresh weight of harvest, root length, and dry weight of brackets. While those that have no significant effect are the wet weight of the roots. The results showed that between LED irradiation treatment L1, L2, L3, and L4 showed that treatment L2 with 80% blue spectrum composition: 20% red showed better growth based on: high plant, chlorophyll content, and root length. Treatment with L4 with white LED showed better growth based on the number of leaves, leaf area, fresh weight of harvest, root wet weight, and dry weight of total biomass. The results below the sunlight better than the LED irradiation treatment, because the intensity of LED far low and lack of controlled environmental conditions technology and management for growing lettuce. In all of LED treatment still looked etiolation because light intensity was not optimal yet.